Erector Spinae Plane (ESP) Block for Postoperative Pain Management after Open Oncologic Abdominal Surgery - Michael Dubilet; Benjamin F. Gruenbaum; Michael Semyonov; Shlomo Yaron Ishay; Anton Osyntsov; Michael Friger; Alexander Geftler; Alexander Zlotnik; Evgeni Brotfain (Pain Research and Management)
Patients undergoing abdominal oncologic surgical procedures require particular surgical and anesthesiologic considerations. Traditional pain management, such as opiate treatment, continuous epidural analgesia, and non-opioid drugs, may have serious side effects in this patient population. We evaluated erector spinae plane (ESP) blocks for postoperative pain management following elective oncologic abdominal surgeries. In this single-center, prospective, and randomized study, we recruited 100 patients who underwent elective oncological abdominal surgery between December 2020 and January 2022 at Soroka University Medical Center in Beer Sheva, Israel. We compared postoperative pain levels in patients who were treated with a preincisional ESP block in addition to traditional pain management with intravenous opioids, non-steroidal anti-inflammatory drugs (NSAIDs), and acetaminophen, compared to patients who were only given traditional pain management (control). Patients who were treated with a preincisional ESP block demonstrated significantly lower Visual Analog Scale scores at 60 minutes and 4, 8, and 12 hours following the surgery, compared to the control group (p<0.001). Accordingly, patients in the ESP group required less morphine from 60 minutes to 12 hours after surgery, but they required increased non-opioid postoperative analgesia management at 4, 8, and 12 hours after surgery (p from 0.002 to <0.001) compared to the control group. In this study, we found ESP blocks to be a safe, technically simple, and effective treatment for postoperative pain management after elective oncologic abdominal procedures.